INDIAN TUNAS—A PRELIMINARY REVIEW, WITH A KEY FOR THEIR IDENTIFICATION - Jones, S; Silas, E G (Indian Journal of Fisheries, 2016)
UNTIL recently only scant attention has been paid to the study of Scombroidfishes in general and tunas in particular occurring in the Indian Seas. Thattunas form an untapped resource awaiting exploitation needs hardly anystress. Year.after year, Japanese fishing vessels operating in the high seasoff Indian coast and other parts of the Indian Ocean reap rich harvests agwill be evident from reports of catch statistics published by them (Averageyears fishing condition of tuna long line fisheries by the Nankai RegionalFisheries Laboratory and other publications emenating from Japan).